2018
DOI: 10.3899/jrheum.180477
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying Persons with Axial Spondyloarthritis At Risk of Poor Work Outcome: Results from the British Society for Rheumatology Biologics Register

Abstract: Objective.First, to test the hypothesis that, among working patients with axial spondyloarthritis (axSpA), those who report issues with reduced productivity at work (presenteeism) are at higher risk of work absence (absenteeism), and patients who report absenteeism are at higher risk of subsequently leaving the workforce. Second, to identify characteristics of workers at high risk of poor work outcome.Methods.The British Society for Rheumatology Biologics Register in Ankylosing Spondylitis has recruited patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 30 publications
(21 reference statements)
5
32
3
3
Order By: Relevance
“…1187 patients were included in our study. We found the employment rate in patients with axSpA in China is 66.81% is higher than the rate in England, which was 62% [17]. The patients in our research were much younger than those in the English study.…”
Section: Discussioncontrasting
confidence: 60%
“…1187 patients were included in our study. We found the employment rate in patients with axSpA in China is 66.81% is higher than the rate in England, which was 62% [17]. The patients in our research were much younger than those in the English study.…”
Section: Discussioncontrasting
confidence: 60%
“…Our findings concur with studies done in Western populations. Studies in axSpA and ankylosing spondylitis populations have previously shown that increased disease activity was associated with presenteeism and activity impairment . Other studies have demonstrated that decreased physical function was associated with work productivity loss and activity impairment, and poorer quality of life with absenteeism, presenteeism, work productivity loss and activity impairment …”
Section: Discussionmentioning
confidence: 98%
“…The type of employment and its impact on work outcomes were not evaluated in this study. This would be important to evaluate in future as work nature does have negative impact on work outcomes in axSpA, particularly blue collar workers with manual work . In addition, further studies to look at reasons on unemployment for patients with axial SpA would be important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of 1188 patients who were working at the time of recruitment to a British axSpA cohort (BSRBR-AS) [21], the authors investigated whether presenteeism was associated with future absenteeism, and whether absenteeism was a risk factor for later leaving the workforce. The data supported both hypotheses.…”
Section: Discussionmentioning
confidence: 99%